Bio-optical temperature sensor and preparation method and application thereof

Through the dumbbell-shaped structure of rare earth-doped nanoparticles loaded on nano-gold rods, the local electric field is used to enhance near-infrared luminescence, which solves the problems of insufficient luminescence intensity and low sensitivity of existing nanoprobes, and achieves efficient temperature monitoring, which is particularly suitable for for photothermal treatment.

CN119286520AActive Publication Date: 2025-01-10SHENZHEN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411406393.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The existing near-infrared second-zone luminescence/temperature measurement nanoprobes have weak near-infrared luminescence intensity and low temperature measurement sensitivity, making it impossible to achieve efficient and accurate temperature monitoring.

Method used

Using composite nanoprobes, including nano-gold rods and rare-earth doped nanoparticles, the local electric field generated by nano-gold rods is used to enhance the near-infrared emission of rare-earth doped nanoparticles through a specific dumbbell-type structure, improve emission intensity and improve temperature sensing sensitivity. .

Benefits of technology

It significantly enhances the near-infrared luminescence intensity, improves the absolute and relative sensitivity of temperature sensing, and achieves efficient temperature monitoring in the range of 313-343K, especially suitable for photothermal therapy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286520A_ABST
    Figure CN119286520A_ABST
Patent Text Reader

Abstract

The invention discloses a biological optical temperature sensor and a preparation method and application thereof, and belongs to the technical field of advanced nonferrous metal materials. The composite nanoprobe comprises a gold nanorod and rare earth doped nanoparticles, mesoporous silica coats the two ends of the gold nanorod, the rare earth doped nanoparticles are loaded on the surface and in holes of the mesoporous silica, and the composite nanoprobe is of a dumbbell-shaped structure; the rare earth doped nano-particles are Gd2O3 nano-particles doped with Yb < 3 + >, Er < 3 + > and Ho < 3 + > metal ions. According to the composite nanoprobe disclosed by the invention, through a specific dumbbell-shaped structure, the luminescence of the rare earth doped nanoparticles loaded at the two ends of the gold nanorod in a near-infrared second region is enhanced by utilizing a dumbbell-shaped surface local electric field generated by the gold nanorod, and the emission intensity is enhanced. The composite nanoprobe provided by the invention can be used for preparing a biological optical temperature sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of advanced nonferrous metal materials, and more specifically, to a bio-optical temperature sensor and a preparation method and application thereof. Background Art

[0002] In recent years, the incidence of cancer has continued to rise, and the incidence of cancer is increasingly tending to be younger, becoming the number one killer threatening human life and health. At present, the main methods of treating tumors include chemotherapy and radiotherapy. In recent years, photothermal therapy has also become a new treatment direction. Photothermal therapy (PTT) refers to the conversion of near infrared (NIR) photon energy absorption into heat by photothermal therapy agents (PTA). Photothermal therapy destroys cell membranes and proteins in tumor tissues through appropriate high temperatures, causing irreversible damage to its cells, thereby achieving low-traumatic and high-precision treatment. Compared with traditional chemotherapy, surgery and radiotherapy, photothermal therapy has the advantages of fast treatment speed and less harm to the human body.

[0003] In the photothermal therapy process of the prior art, the therapeutic effect depends on the heat converted by the photothermal therapeutic agent when absorbing the energy of near-infrared light irradiation. However, due to the inevitable heat diffusion during photothermal therapy, the temperature of the edge of the tumor tissue will decrease, while the temperature of the surrounding normal tissue will increase. If the eradication of the tumor is pursued, the excitation light power needs to be increased to make the temperature of the tumor edge high enough, but this will accidentally damage the normal tissue; if the laser power is reduced too much to ensure that the normal tissue is not damaged, then some tumor cells will survive. Therefore, to achieve effective and safe photothermal therapy, it is necessary to accurately control the tissue temperature and have a real-time temperature monitoring system. Temperature detection of the target treatment area can not only effectively avoid incomplete treatment due to insufficient heat and damage to normal tissues due to excessive heat during photothermal therapy, but also improve the safety and efficiency of photothermal therapy, and help us better understand the internal conditions of the human body. Because traditional temperature measurement methods (such as mercury thermometers, thermocouple thermometers and thermal imagers, etc.) are limited by the structure of human tissues and measurement tools, it is impossible to accurately and non-invasively measure their internal temperature. Only by creatively inventing new temperature measurement methods can efficient, accurate and non-contact temperature monitoring be achieved.

[0004] After being excited, the electrons in the 4f energy level of rare earth ions transition to lower energy levels by radiation relaxation and emit light of various wavelengths. Rare earth ion luminescence has the characteristics of low photobleaching, large anti-Stokes frequency shift, and narrow light emission peak. Therefore, it shows broad application prospects in the fields of biomedical imaging and treatment, temperature sensing, solar cells, and printing anti-counterfeiting processing.

[0005] Rare earth ions can be used for temperature measurement, which is based on the microscopic properties of rare earth ions. According to the temperature dependence of energy transfer (ET) and multi-phonon relaxation (MPR) in the luminescence process of rare earth ions, when the temperature rises, the transfer efficiency and relaxation rate both increase, thereby affecting the luminescence intensity and fluorescence lifetime. Therefore, rare earth-doped nanoparticles can be used as optical temperature sensors, and have the characteristics of non-contact, high sensitivity and spatial resolution, and rapid response. For different rare earth ions, due to their different energy level distributions, their ET and MPR efficiencies are different, and the relative change rates affected by temperature are also different.

[0006] Therefore, based on the principle of rare earth nanothermometer, the luminescence intensity ratio can be used to monitor the temperature of tumor tissue, so that the tissue temperature during photothermal therapy can be monitored in real time, and a real-time isotherm diagram can be formed to observe the heat diffusion between tumor and normal tissue during photothermal therapy, providing some reference for the control of excitation light power.

[0007] Most of the temperature probes used in previous photothermal therapy were excited by visible light, but visible light cannot penetrate thick biological tissues. In recent years, it has been found that the near-infrared II region (NIR-II) has unique advantages in the biomedical field, which has a huge role in promoting the optical imaging of biological tissues, diagnosis and treatment of diseases, especially for the in-depth understanding of the dynamic information of the molecular level activities of organisms.

[0008] Prior art CN113801653A discloses a near-infrared second-zone luminescent / temperature measuring nanoprobe, comprising a SiO2 core and four shell layers coated on the SiO2 core, wherein the shell layers are an activation layer, a transition layer, a sensitizing layer and an inert layer from the inside to the outside; the activation layer is doped with Er 3+ and Yb 3+ The transition layer is doped with Yb 3+ The sensitizing layer is doped with Nd 3+ and Yb 3+ The inert layer is a Gd2O3 layer. The emission wavelength of the nanoprobe is in the near-infrared region II and can be applied to nano-temperature sensors. However, the near-infrared luminescence intensity of the nanoprobe is weak, and the maximum temperature measurement sensitivity of temperature sensing based on the near-infrared emission intensity is only 1.29% K. -1 , while the maximum temperature sensitivity around 313-343K is only 0.12%K -1 . Summary of the invention

[0009] The technical problem to be solved by the present invention is that the existing near-infrared second-zone luminescence / temperature measurement nanoprobes have defects and shortcomings such as poor near-infrared luminescence intensity and low temperature measurement sensitivity. A composite nanoprobe is provided to improve the near-infrared photoluminescence intensity and have higher temperature measurement sensitivity.

[0010] Another object of the present invention is to provide a method for preparing a composite nanoprobe.

[0011] Another object of the present invention is to provide a bio-optical temperature sensor.

[0012] Another object of the present invention is to provide a bio-optical temperature sensor for application in bio-optical temperature measurement.

[0013] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0014] A composite nanoprobe, comprising a nanogold rod and rare earth-doped nanoparticles, wherein both ends of the nanogold rod are coated with mesoporous silica, the surface and pores of the mesoporous silica are loaded with the rare earth-doped nanoparticles, and the composite nanoprobe has a dumbbell-shaped structure;

[0015] Wherein, the rare earth doped nanoparticles are Gd2O3 nanoparticles doped with Yb 3+ , Er 3+ and Ho 3+ Metal ions.

[0016] The composite nanoprobe of the present invention, through a specific dumbbell-shaped structure, utilizes the dumbbell-shaped surface local electric field generated by the nanogold rod to enhance the luminescence of rare earth-doped nanoparticles loaded at both ends of the nanogold rod in the second near-infrared region, thereby enhancing the emission intensity.

[0017] Among them, it should be noted that:

[0018] The composite nanoprobe of the present invention, the rare earth doped nanoparticles can emit near-infrared second zone fluorescence under the irradiation of excitation light, and the strong absorption of excitation light by the nano-gold rod and the longitudinal surface plasmon resonance characteristics generate a dumbbell-shaped local electric field at both ends of the gold rod, which can react with the excitation field and Yb 3+ The absorption forms a ternary resonance, and the induced local electric field can greatly enhance the photoluminescence properties of rare earth-doped nanoparticles in the near-infrared second region.

[0019] The composite nanoprobe of the present invention has a dumbbell-shaped structure. The local electric field on the surface of the composite nanoprobe presents a dumbbell-shaped distribution, which is consistent with the local electric field distribution generated by the gold nanorod. It can maximize the coverage of rare earth-doped nanoparticles, maximize the enhancement of rare earth photoluminescence, and improve the near-infrared photoluminescence intensity of the probe.

[0020] The composite nanoprobe of the present invention utilizes the temperature dependence characteristics of energy level transitions of rare earth luminescent ions (erbium ions and holmium ions) in the near-infrared second region, and performs near-infrared second region optical temperature sensing based on the changes in near-infrared fluorescence intensity, fluorescence intensity ratio and fluorescence lifetime with temperature, showing excellent photostability and relative sensitivity of temperature sensing.

[0021] Preferably, in the rare earth-doped nanoparticles, Gd 3+ , Yb 3+ , Er 3+ and Ho 3+ The molar ratio is (80~96) : (2~18) : (0.2~4) : (0.2~4).

[0022] In order to further improve the luminescence intensity and relative sensitivity of optical temperature sensing of the composite nanoprobe, preferably, in the rare earth doped nanoparticles, Gd 3+ , Yb 3+ , Er 3+ and Ho 3+ The molar ratio is (91-95):(5-10):(0.5-1.5):(0.5-1.5).

[0023] More preferably, in the rare earth doped nanoparticles, Gd 3+ , Yb 3+ , Er 3+ and Ho 3+ The molar ratio is 92:6:1:1.

[0024] Preferably, in the composite nanoprobe, the atomic ratio of rare earth element to gold element is (0.3-0.9):1.

[0025] The rare earth elements include rare earth doped nanoparticles on the surface of mesoporous silica and in the pores of mesoporous silica.

[0026] More preferably, in the composite nanoprobe, the atomic ratio of rare earth element to gold element is (0.6-0.85):1.

[0027] The present invention also protects a method for preparing the composite nanoprobe, comprising the following steps:

[0028] S1. Prepare gold nanorod solution and rare earth doped nanoparticles respectively;

[0029] S2. Covering both ends of the gold nanorods in S1 with mesoporous silica;

[0030] S3. Ultrasonic oscillate the mesoporous silica-coated nanogold rod solution of S2 and the nano rare earth particles of S1 to obtain the composite nanoprobe.

[0031] In the present invention:

[0032] The preparation method of the gold nanorod solution may be an existing preparation method, such as a seed growth method.

[0033] The preparation method of rare earth doped nanoparticles may be an existing preparation method, such as a high boiling point polyol dehydration direct colloidal precipitation method.

[0034] In step S2 of the present invention, mesoporous silica can be covered on both ends of the nano-gold rods by a sol-gel method with controlled surfactant, and the silica pores can be cleaned by refluxing in a hydrochloric acid ethanol solution and activating the surface dangling bonds.

[0035] The invention anchors rare earth doped nanoparticles in the mesoporous silica pores and on the surface of the mesoporous silica through ultrasonic oscillation nano cascade assembly technology.

[0036] The preparation method of the nano-gold rod solution may include the following steps: Preparation of seed solution: dissolve hexadecyl trimethyl ammonium bromide in deionized water, add chloroauric acid solution and sodium borohydride (NaBH4) ice water solution, stir, and stand to obtain a nano-gold rod seed solution. Preparation of growth solution: dissolve hexadecyl trimethyl ammonium bromide in deionized water, add chloroauric acid solution, AgNO3 solution and HCl in sequence, and add ascorbic acid during stirring. Stir the solution until it is colorless, add the prepared seed solution and stir gently, and let the solution stand. Collect by centrifugation, remove the supernatant, and disperse in deionized water to obtain a nano-gold rod solution.

[0037] The preparation of rare earth doped nanoparticles may include the following steps: taking a rare earth aqueous solution and diethylene glycol, vigorously stirring in an oil bath, adding a NaOH aqueous solution, heating, stirring to obtain a light yellow colloidal solution, adding an appropriate amount of deionized water to the solution, centrifuging, and drying the precipitate in a drying oven to obtain rare earth doped nanoparticles.

[0038] Covering the two ends of the nano-gold rods of S1 with mesoporous silica may include the following steps: taking the nano-gold rod solution, adding CTAB, ultrasonically dispersing it in deionized water, and adding NaOH solution. Adding TEOS ethanol solution during slow stirring, and continuing stirring. Centrifuging, washing with alcohol and deionized water. Dispersing the obtained solid in the CTAB aqueous solution, adding NaOH solution, and adding TEOS ethanol solution during slow stirring. Centrifuging, washing with hydrochloric acid ethanol solution and deionized water.

[0039] Step S3 of the present invention may include the following steps: mixing a nanogold rod solution with mesoporous silica at both ends, a nanorare earth particle solution and deionized water, ultrasonicating, oscillating, centrifuging and collecting, and then washing with anhydrous ethanol and deionized water to obtain the composite nanoprobe.

[0040] The present invention also protects a bio-optical temperature sensor, comprising any of the composite nanoprobes described above.

[0041] The present invention also protects the application of the above-mentioned bio-optical temperature sensor in bio-optical temperature measurement.

[0042] The bio-optical temperature sensor of the present invention can be used to monitor biomedical diagnosis and treatment, and is particularly suitable for bio-optical temperature measurement. For example, optical temperature sensing can use photoelectric signals to perform non-contact real-time monitoring of the temperature of the tumor site. Since the luminescence energy level of rare earth luminescence is temperature-dependent, the luminescence intensity ratio or fluorescence lifetime can be used to monitor the temperature of the tumor tissue and perform real-time photothermal therapy.

[0043] The bio-optical temperature sensor of the present invention can be used for simultaneous diagnosis, treatment and monitoring of tumors.

[0044] Preferably, the temperature of the temperature measurement is 313-343K.

[0045] The bio-optical temperature sensor of the present invention can realize temperature measurement in the range of 313-343K, is particularly suitable for the temperature range of 313-343K photothermal therapy, and has extremely high absolute sensitivity and relative sensitivity.

[0046] Preferably, in the temperature measurement, the excitation light wavelength of the bio-optical temperature sensor is 900-1100 nm.

[0047] The bio-optical temperature sensor of the present invention can use near-infrared light with an excitation wavelength of 980nm as excitation light. The excitation wavelength is within the biological transparent window of 680-1100nm, in which soft tissue will not strongly absorb or scatter. Therefore, rare earth ions can be excited at a higher tissue depth than the ultraviolet-visible light excitation source. The wavelengths of the two lights (1201nm and 1535nm) converted after being absorbed by the probe are in the near-infrared second region NIR-II, and have a stronger ability to penetrate human tissue, thereby completing the temperature measurement function.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] The composite nanoprobe of the present invention, through a specific dumbbell-shaped structure, utilizes the dumbbell-shaped surface local electric field generated by the nanogold rod to enhance the luminescence of rare earth-doped nanoparticles loaded at both ends of the nanogold rod in the near-infrared second region, thereby enhancing the emission intensity, and the luminescence intensity is enhanced by two orders of magnitude.

[0050] The composite nanoprobe of the present invention utilizes the temperature dependence characteristics of energy level transition of rare earth luminescent ions (erbium ions and holmium ions) in the near-infrared zone II, and performs near-infrared zone II optical temperature sensing based on the change of near-infrared fluorescence intensity, fluorescence intensity ratio and fluorescence lifetime with temperature, showing excellent photostability, temperature sensing absolute sensitivity and temperature sensing relative sensitivity. The relative sensitivity based on the 1201nm holmium ion emission light lifetime at 338K is as high as 7.25%K -1 The relative sensitivity of the 1535nm erbium ion emission lifetime at 343K is 5.38% K. -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 a is an electron microscope image of the rare earth-doped nanoparticles in Example 1.

[0052] Figure 1 b is a high-resolution electron microscope image of a single particle of the rare earth-doped nanoparticles in Example 1.

[0053] Figure 1 c, Figure 1 d is Figure 1 a. Fourier transform and inverse Fourier transform of rare earth-doped nanoparticles.

[0054] Figure 1 e and Figure 1 f is the TEM image and EDS spectrum of the composite nanoprobe of Example 1.

[0055] Figure 1 g- Figure 1 k is the line scan and element scan of the composite nanoprobe EDS spectrum of Example 1.

[0056] Figure 2 a is the absorption spectrum of the gold nanorod and the composite nanoprobe of Example 1.

[0057] Figure 2 b is the emission spectra of the composite nanoprobe of Example 1 and the rare earth-doped nanoparticles of Comparative Example 1.

[0058] Figure 2 c is the luminescence energy level diagram of the composite nanoparticles of Example 1.

[0059] Figure 3 a is the NIR absorption cross section simulated using the finite-difference time-domain (FDTD) algorithm.

[0060] Figure 3 b is the electric field enhancement curve along the x-axis under different incident excitations.

[0061] Figure 3 c is the simulated structural model of the nanoprobe.

[0062] Figure 3 d is the local electric field E distribution.

[0063] Figure 4 a, Figure 4 b is the emission spectra of the composite nanoprobe of Example 1 measuring six temperature gradients of 313-343K and the curves of the emission peak intensity at 1201nm and 1535nm changing with temperature.

[0064] Figure 4 c is the relative sensitivity of the composite nanoprobe of Example 1 in each NIR-II single peak luminescence intensity and luminescence intensity ratio.

[0065] Figure 4 d is the five cycles of heating and cooling measured by the composite nanoprobe of Example 1 based on ratio fluorescence temperature measurement.

[0066] Figure 5 a, Figure 5 b is the curve of the change of the emission peak fluorescence lifetime of the composite nanoprobe of Example 1 at 1201nm and 1535nm at six temperature gradients of 313-343K.

[0067] Figure 5 c is the variation law of the luminescence lifetime of the composite nanoprobe in Example 1 with temperature.

[0068] Figure 5 d is the relative sensitivity curve of the composite nanoprobe optical temperature sensing of Example 1.

[0069] Figure 5 e and Figure 5 f is the 1201 nm emission lifetime and 1535 nm emission lifetime of the composite nanoprobe of Example 1 at 313 K and 343 K in five cycles.

[0070] In the accompanying drawings, "AuNRs" refers to gold nanorods.

[0071] "Gd2O3:Yb 3+ / Er 3+ / Ho 3+ ” refers to rare earth-doped nanoparticles.

[0072] “AuNR@Gd2O3:Yb 3+ / Er 3+ / Ho 3+ ” refers to composite nanoprobe. DETAILED DESCRIPTION

[0073] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0074] Example 1

[0075] A composite nanoprobe comprises a nanogold rod and rare earth-doped nanoparticles, wherein both ends of the nanogold rod are coated with mesoporous silica, the surface and pores of the mesoporous silica are loaded with rare earth-doped nanoparticles, and the composite nanoprobe has a dumbbell-shaped structure;

[0076] Among them, the rare earth doped nanoparticles are Gd2O3 nanoparticles doped with Yb 3+ , Er 3+ and Ho 3+ Metal ions, rare earth doped nanoparticles, Gd 3+ , Yb 3+ , Er 3+ and Ho 3+ The molar ratio is 92:6:1:1;

[0077] In the composite nanoprobe, the atomic ratio of rare earth elements to gold elements is 0.82:1.

[0078] The preparation method of the composite nanoprobe comprises the following steps:

[0079] S1. Preparation of gold nanorods: Preparation of seed solution: Dissolve 0.364g of hexadecyltrimethylammonium bromide (CTAB) in 9.17mL of deionized water, add 242μL of 0.012386mol / L chloroauric acid solution, add 0.58mL of 0.02mol / L sodium borohydride (NaBH4) ice water solution, immediately stir rapidly (350r / min) for two minutes, and let stand in a 27°C water bath for 2h to obtain a gold nanorod seed solution. Preparation of growth solution: Dissolve 1.82g of CTAB in 44mL of deionized water, add 2.907mL of 0.012386mmol / L chloroauric acid solution, 1.04mL of 0.005mol / L AgNO3 solution and 0.4mL of HCl (37%) in sequence, and add 1.64mL of 0.05mol / L ascorbic acid during stirring. After the solution is stirred until colorless, 50uL of the prepared seed solution is added and gently stirred for 10s (110r / min), and the solution is placed in a 27°C water bath for 12h. Centrifuge at 10000r / min for 15 minutes, collect, remove the supernatant, and disperse in 25mL of deionized water to obtain a gold nanorod solution.

[0080] Preparation of rare earth doped nanoparticles: Take 20mL of 0.2mol / L rare earth aqueous solution (molar ratio Gd 3+:Yb 3+ :Er 3+ :Ho 3+ =92:6:1:1) and 20mL diethylene glycol (DEG) in a conical flask, stir vigorously in an 80℃ oil bath for 1h (750rpm), and quickly add 1mL NaOH aqueous solution (0.1mol / L). Heat to 140℃ and stir for another 1h, heat to 180℃ and stir for another 4h to obtain a light yellow colloidal solution. Add appropriate amount of deionized water to the solution, centrifuge it with a centrifuge, centrifuge it at 2500rpm for 10min, pour out the supernatant, add appropriate amount of deionized water and centrifuge it at 10000rpm for 7min twice. After centrifugation, put the precipitate into a drying oven to dry to obtain rare earth doped nanoparticles.

[0081] S2. Cover both ends of the gold nanorods in S1 with mesoporous silica:

[0082] Take the nanogold rod solution prepared in the previous step, centrifuge it twice at 9000r / min, remove the supernatant, add 0.008g CTAB, ultrasonically disperse it in 40mL deionized water, and add 0.4mL 0.025mol / L NaOH solution. Add 0.4mL of 4% (volume fraction) TEOS ethanol solution every 30min during slow stirring, add it 4 times in total, and continue stirring for 12h. Centrifuge, wash once with alcohol and then with deionized water, and repeat this three times. Dissolve 0.029g CTAB in 40mL deionized water, ultrasonically disperse the obtained AuNR@SiO2 in this CTAB solution, add 0.5mL 0.025mol / L NaOH solution, add 0.8mL of 8% (volume fraction) TEOS ethanol solution every 30min during slow stirring, and add it 4 times in total. Centrifuge, wash twice with hydrochloric acid ethanol solution and deionized water respectively.

[0083] S3. Mix 5 mL of the nanogold rod solution obtained in step S2 after centrifugal washing, 1 mL of the 0.2 mol / L nano rare earth particle solution obtained in step S1, and 4 mL of deionized water, ultrasonicate for 3 h at room temperature, and stir by oscillation for 3 h. Collect by centrifugation (10000 rpm, 20 min), wash once with anhydrous ethanol, and wash once with deionized water to obtain a composite nanoprobe, which is stored in 10 mL of deionized water.

[0084] Example 2

[0085] A composite nanoprobe, which differs from Example 1 in that: in the rare earth doped nanoparticles, Gd 3+ , Yb 3+ , Er 3+ and Ho 3+ The molar ratio is 90:6:2:2.

[0086] The difference between the preparation method and Example 1 is that step S1: 20 mL 0.2 mol / L rare earth aqueous solution of Gd 3+ , Yb 3+ , Er 3+ and Ho 3+ The molar ratio is =90:6:2:2.

[0087] Example 3

[0088] A composite nanoprobe, which is different from Example 1 in that: in the composite nanoprobe, the atomic ratio of rare earth element to gold element is 0.4:1.

[0089] The difference between the preparation method and Example 1 is that step S3: 5 mL of the nanogold rod solution obtained in step S2 after centrifugation and washing, 0.5 mL of the 0.2 mol / L nano rare earth particle solution obtained in step S1, and 4 mL of deionized water are mixed.

[0090] Comparative Example 1

[0091] A rare earth-doped nanoparticle, the preparation method of which is the same as that of the rare earth-doped nanoparticle in Example 1.

[0092] Results

[0093] The composite nanoprobes of the above embodiments and comparative examples were tested for relevant properties:

[0094] Figure 1 a is an electron microscope image of the rare earth-doped nanoparticles in Example 1. It can be seen that the size of the rare earth-doped nanoparticles is about 3 nm, and they have good dispersibility and uniformity. Figure 1 b is a high-resolution electron microscope image of a single rare earth-doped nanoparticle in Example 1. It can be seen that the single rare earth-doped nanoparticle has obvious lattice fringes, which proves the excellent crystallization characteristics of the particle. Figure 1 c, Figure 1 d is Figure 1 From the Fourier transform and inverse Fourier transform diagrams of the rare earth-doped nanoparticles in a, it can be observed that the two-dimensional lattices of the rare earth-doped nanoparticles are mostly of the crystal plane index 420 and 123 type, and are cubic crystal phase particles.

[0095] Figure 1 e and Figure 1 f is the TEM image and EDS spectrum of the composite nanoprobe of Example 1, which proves that the composite nanoprobe has a dumbbell morphology, the atomic ratio of rare earth elements to gold elements is about 4:5, and the composite nanoprobe has an excellent rare earth loading rate. Figure 1 g- Figure 1k is the line scan and element scan of the composite nanoprobe EDS spectrum of Example 1, indicating that the rare earth-doped nanoparticles are more loaded on the surface of the mesoporous silica.

[0096] Figure 2 a is the absorption spectrum of the gold nanorods and the composite nanoprobe of Example 1, indicating that the absorption peak of the composite nanoprobe is red-shifted relative to that of the rare earth-doped nanoparticles, and has strong absorption near 940 nm.

[0097] Figure 2 b is the emission spectrum of the composite nanoprobe of Example 1 and the rare earth-doped nanoparticles of Comparative Example 1. The integrated intensity ratio (i.e., enhancement factor EF) of the number of emitted photons of the composite nanoprobe formed by the rare earth-doped nanoparticles of Example 1 relative to the single rare earth-doped nanoparticles of Comparative Example 1 is 1. 3+ The emission peak is 97.2, while at Er 3+ The emission peak is enhanced by 102, indicating that the integrated intensity of emitted photons after rare earth-doped nanoparticles are loaded on both ends of the gold nanorods is increased by about 100 times after removing the dark current background.

[0098] Figure 2 c is the luminescence energy level diagram of the composite nanoprobe of Example 1. It shows that the Yb doped in the rare earth doped nanoparticles 3+ The ions can absorb the 980nm excitation light and undergo energy level transitions through energy transfer (ET) and multi-phonon relaxation (MPR) between the internal energy levels of the ions, making Er 3+ with Ho 3+ The ions emit near-infrared IIb light at 1201nm and 1535nm, respectively, achieving optical conversion in the near-infrared region. Due to the strong absorption of the gold nanorods near 980nm, the excitation field can be greatly enhanced, and the existence of the Purcell effect may lead to slight differences in the luminescence enhancement amplitude of the emitted light at 1201nm and 1535nm.

[0099] The finite difference time domain method (FDTD) was used to calculate the surface local electric field distribution of the composite nanoprobe of Example 1 under different structural parameter conditions. Figure 3 a is the NIR absorption cross section simulated by the finite-difference time-domain (FDTD) algorithm. The simulated absorption cross section of the composite nanoprobe has a peak at 950nm, which is basically consistent with the longitudinal absorption peak measured experimentally. Figure 3 b is the electric field enhancement curve along the x-axis under different incident excitations. When the incident excitation wavelength is 980nm, the fixed Y position is 56nm, and the Z position is 0nm (i.e., at the outer surface of the composite nanoparticles), the electric field along the x-axis is significantly enhanced. Figure 3 c is the simulated structural model of the composite nanoprobe, Figure 3d is the corresponding local electric field E distribution, indicating that the local electric field enhancement is mainly distributed at the two ends of the composite nanoprobe, which is consistent with the dumbbell-shaped probe structure. It shows that the rare earth doped particles are mainly distributed in the local electric field enhancement range, which can maximize the use of local electric field to enhance rare earth photoluminescence. The excitation light wavelength of 980nm is also close to the longitudinal near-infrared resonance peak of the composite nanoprobe. The charge separation caused by the surface plasmon resonance effect is more obvious, and the dumbbell end Yb 3+ The excitation efficiency of ions is improved, so the gold nanorods promote the improvement of near-infrared photoluminescence efficiency.

[0100] According to the temperature dependence of energy transfer and multi-phonon relaxation, temperature changes will significantly affect the particle population of each energy level of rare earth ions, change the energy transfer efficiency and non-radiative relaxation rate, and thus affect the luminescence intensity and fluorescence lifetime. The present invention evaluates the temperature sensing properties of the prepared composite nanoprobe by measuring the emission spectrum generated by the sample excited by 980nm near-infrared light of the same power and the fluorescence lifetime at the stimulated emission peak (1201nm and 1535nm) under different temperature conditions. Figure 4 a, Figure 4 b is the emission spectra of the composite nanoprobe of Example 1 at six temperature gradients of 313-343K and the curve of the emission peak intensity at 1201nm and 1535nm as a function of temperature. It can be seen that as the temperature increases from 313K to 343K, the peak intensity at 1201nm Ho 3+ and 1535nm Er 3+ The emission intensity near the two emission peaks decreases with increasing temperature and has a certain monotonicity. The change of light intensity at 1201nm with temperature basically conforms to the law of monotonous decrease, and shows a certain linear characteristic in this range, while the change of light intensity at 1535nm with temperature basically conforms to the law of exponential decrease. Taking the logarithm of the light intensity at 1535nm, the ratio of the logarithm of the light intensity at 1201nm and the light intensity at 1535nm at different temperatures is linear, and the error is small, which is very helpful for calibrating temperature measurement.

[0101] Relative sensitivity (Sr) is an important parameter for quantitatively evaluating the performance of optical temperature sensors. It can compare the advantages and disadvantages of different temperature measurement methods and is usually defined as: Sr = (1 / SP) | dSP / dT | × 100%. SP represents the spectral parameters used for temperature sensing, including single-peak luminescence intensity, double-peak luminescence intensity ratio, and single-peak fluorescence lifetime. Figure 4 c is the relative sensitivity of the composite nanoprobe in each NIR-II single peak luminescence intensity and luminescence intensity ratio of Example 1. As the temperature increases, they all increase monotonically. The temperature measurement sensitivity based on 1535nm in the near infrared II region is as high as 7.45% K at 343K. -1The intensity ratio also has a high temperature measurement sensitivity, reaching 3.94% K at 343 K. -1 Ratio-type nanothermometry avoids the influence of fluorescence attenuation and rare earth-doped nanoparticle concentration by measuring two fluorescence signals simultaneously, and can obtain more accurate and reliable information than single emission intensity. Figure 4 d is the five cycles of heating and cooling measured by the composite nanoprobe in Example 1 based on ratio fluorescence thermometry. The fluorescence intensity ratio of the composite nanoprobe remains basically unchanged in the high temperature section and the low temperature section, proving that the composite nanoprobe prepared in Example 1 has excellent optical temperature sensing stability.

[0102] Fluorescence lifetime is a spectral parameter that characterizes the fluorescence decay rate. It is independent of the concentration of the nanoprobe, the irradiation power of the exogenous excitation light, and the medium through which the fluorescence penetrates. It is determined by the intrinsic properties of the nanoprobe itself, such as its structural composition. Therefore, optical temperature sensing based on fluorescence lifetime is also a very stable temperature measurement method. Figure 5 a, Figure 5 b is the curve of the change of the emission peak fluorescence lifetime of the composite nanoprobe of Example 1 at 1201nm and 1535nm at six temperature gradients of 313-343K. The change of the luminescence lifetime of the composite nanoprobe with temperature basically conforms to the exponential increasing law ( Figure 5 c). Relative sensitivity curve of composite nanoprobe optical temperature sensing ( Figure 5 d) The relative sensitivity of the 1201nm emission lifetime at 338K is as high as 7.25%K -1 The relative sensitivity based on the lifetime of 1535nm emission light at 343K also reaches 5.38% K -1 At the same time, the 1201nm emission lifetime and 1535nm emission lifetime values ​​of 313K and 343K under five cycles were detected and remained basically unchanged ( Figure 5 e and Figure 5 f). 313-343K is the temperature range of photothermal therapy. The composite nanoprobe shows extremely high optical temperature sensing sensitivity in this range, that is, the composite nanoprobe prepared in Example 1 has good optical temperature sensing application.

[0103] It can be seen from Example 1 and Comparative Example 1 that in the composite nanoprobe with a specific structure of the present invention, the surface local electric field generated by the nanogold rod can enhance the near-infrared second-region luminescence of the rare earth-doped nanoparticles loaded at both ends of the nanogold rod, and the luminescence intensity is increased by two orders of magnitude.

[0104] The luminescence intensity and relative sensitivity of optical temperature sensing of the composite nanoprobe obtained in Example 2 are slightly lower than those of the composite nanoprobe in Example 1, but significantly better than those of Comparative Example 1.

[0105] The relative sensitivity of optical temperature sensing of the composite nanoprobe obtained in Example 3 is slightly lower than the luminescence intensity and relative sensitivity of optical sensing of the composite nanoprobe in Example 1, but significantly better than the luminescence intensity and relative sensitivity of optical sensing of Comparative Example 1. This may be because the content of rare earth-doped nanoparticles loaded on the surface and in the mesopores of the mesoporous silica in the composite nanoprobe in Example 3 is slightly low, and the ability of the nanogold rod plasmon resonance to enhance the rare earth photoluminescence is slightly reduced, so the relative sensitivity of optical temperature sensing of the composite nanoprobe is slightly reduced.

[0106] In actual temperature measurement applications, the enhanced NIR-II region spectral parameters of the nanoprobe detected by the spectrometer can be directly used for high-resolution fluorescence imaging, and the spectral parameters can achieve high-sensitivity local temperature sensing after specific data conversion.

[0107] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A composite nanoprobe, characterized in that: The composite nanoprobe comprises a nanogold rod and rare earth-doped nanoparticles, both ends of the nanogold rod are coated with mesoporous silica, the surface and pores of the mesoporous silica are loaded with the rare earth-doped nanoparticles, and the composite nanoprobe has a dumbbell-shaped structure; Wherein, the rare earth doped nanoparticles are Gd2O3 nanoparticles doped with Yb 3+ , Er 3+ and Ho 3+ Metal ions.

2. The composite nanoprobe according to claim 1, characterized in that: In the rare earth doped nanoparticles, Gd 3+ , Yb 3+ , Er 3+ and Ho 3+ The molar ratio is (80~96) : (2~18) : (0.2~4) : (0.2~4).

3. The composite nanoprobe according to claim 2, characterized in that: In the rare earth doped nanoparticles, Gd 3+ , Yb 3+ , Er 3+ and Ho 3+ The molar ratio is (91-95):(5-10):(0.5-1.5):(0.5-1.5).

4. The composite nanoprobe according to claim 1, characterized in that: In the composite nanoprobe, the atomic ratio of rare earth element to gold element is (0.3-0.9):

1.

5. The composite nanoprobe according to claim 4, characterized in that: In the composite nanoprobe, the atomic ratio of rare earth element to gold element is (0.6-0.85):

1.

6. The method for preparing the composite nanoprobe according to any one of claims 1 to 5, characterized in that: The steps include: S1. Prepare gold nanorod solution and rare earth doped nanoparticles respectively; S2. Covering both ends of the gold nanorods in S1 with mesoporous silica; S3. Ultrasonic oscillate the mesoporous silica-coated nanogold rod solution of S2 and the nano rare earth particles of S1 to obtain the composite nanoprobe.

7. A bio-optical temperature sensor, characterized in that: It comprises the composite nanoprobe according to any one of claims 1 to 5.

8. Application of the bio-optical temperature sensor according to claim 7 in bio-optical temperature measurement.

9. The use according to claim 8, characterized in that The temperature of the temperature measurement is 313-343K.

10. The use according to claim 8, characterized in that In the temperature measurement, the excitation light wavelength of the bio-optical temperature sensor is 900-1100nm.

Citation Information

Patent Citations

  • Mesoporous silica compound particles containing gold nanorods, preparation method and application thereof

    CN102319435A

  • Multimode magneto-photothermal diagnosis and treatment integrated nano probe as well as preparation method and application thereof

    CN108175859A

  • Composite nanoprobe with dumbbell structure as well as preparation method and application thereof

    CN110974960A